Economic evaluation: costing participatory learning and action cycles with women’s groups to improve feeding, care and dental hygiene for South Asian infants in London - Zhang, Yeqing; Patil, Priyanka; Chaudhary, Shweta; Kondhare, Kunal D.; Faijue, Darlington David; Lakhanpaul, Monica; Heys, Michelle; Drazdzewska, Joanna; Llewellyn, Clare H.; Webb-Martin, Kelley; Irish, Carol; Archibong, Mfon; et al. (Frontiers in Public Health, 2025)
BackgroundThe Nurture Early for Optimal Nutrition (NEON) programme was designed to promote equitable early childhood development by educating mothers of South Asian origin in two boroughs (Newham and Tower Hamlets) in East London on optimal feeding, care, and dental hygiene practices. The study found that the adapted Participatory Learning and Action (PLA) approach was highly acceptable and well-received by participants, with improvements in maternal confidence, infant feeding practices, and community engagement. However, gaps in specific feeding skills and challenges such as low attendance and retention rates were noted, particularly during the COVID-19 pandemic. This study conducted a cost analysis of the NEON programme and evaluated its financial sustainability.MethodsWe conducted a financial and economic costing from the provider perspective, applying a stepdown procedure to identify costs associated with the development and implementation of the NEON programme. Estimates of total and average costs per mother are presented along with affordability assessments, expressed as a proportion of the borough’s annual child development expenditure. All costs were discounted and reported in 2022 pound sterling and in 2022 international dollars.ResultsThe total cost of NEON design and delivery was £68,165 (INT 102,658), and the average cost per mother participating in the programme was £439(INT 661) in the face-to face arm and £407(INT 614) in the online arm. The largest contributor to the total cost was materials (50%), including NEON training manuals and intervention toolkits, vouchers for the community facilitators, and overheads, followed by staff costs (45%) and capital investments (5%). The total cost of intervention delivery in Newham accounted for around 0.047% of the borough’s annual child development expenditure, while the total intervention cost in Tower Hamlets was equivalent to 0.003% of its spending on children’s development.ConclusionThe delivery of NEON is largely within local authorities’ budget for childhood development. The unit cost is expected to decrease when sharing costs are spread across more participants and implementing systems are validated and well developed.